Polarity sensitivity to symmetric, biphasic monopolar pulses is not a reliable indicator of peripheral axonal degeneration in human cochlear implant users - He, Shuman; Oleson, Jacob J.; Gao, Zi (Frontiers in Audiology and Otology, 2025)
This study aimed to determine whether the effect of changing stimulus polarity on the electrically evoked compound action potential (eCAP) threshold—referred to as the polarity effect—could be used to assess the degeneration of the peripheral axon of the cochlear nerve (CN) in human cochlear implant (CI) users. The polarity effect, measured using symmetric, biphasic pulses delivered in a monopolar-coupled stimulation mode, was systematically compared among four cochlear-implanted patient populations with differing CN statuses: children with cochlear nerve deficiency, children with biallelic Gap Junction Beta-2 gene mutations, children with idiopathic sensorineural hearing loss, and postlingually deafened adults with various etiologies. All patients used a Cochlear™ Nucleus® device in the test ear. The differences in the polarity effect across patient groups, as revealed by the results of Linear Mixed-Effect Models (LMMs), were not aligned with known anatomical differences in CN status for these patient groups regardless of quantification method. Therefore, peripheral axonal degeneration is unlikely to be the sole or primary biological contributor to the polarity effect measured using symmetric biphasic pulses in monopolar-coupled stimulation mode in human CI users.